Shadow Play : Eve Duncan #19 - Johansen, Iris (New York : St. Martin's Press, 2015)
"Eve Duncan is the most sought-after artist in the field of forensic sculpting. Dedicated to her work ever since her daughter Bonnie was taken and killed at the age of seven, Eve feels a sense of duty to those whose lives were lost and whose bones are now in her hands. When a sheriff in California contacts her with a request for help on the reconstruction of the skull of a nine-year-old girl whose body has been buried for eight years, his intensity and investment in the case puzzle her. But when the ghost of the girl begins communicating with her, Eve finds herself wrapped up in the case more intensely than she could have ever imagined. Not since Bonnie has Eve had such an experience, and suddenly she finds herself determined to solve the murder and help the little girl find peace. Except that the killer is still out there, and he knows Eve is on the case. And he won't rest until anything and anyone that could reveal his identity is eliminated.."--
Keywords: Duncan, Eve (Fictitious character) -- Fiction; Facial reconstruction (Anthropology) -- Fiction; Women sculptors -- Fiction; Children -- Crimes against -- Fiction; Cold cases (Criminal investigation) -- Fiction; FICTION / Suspense; Mystery fiction; Suspense fiction